Harmoni Multikultural; Keragaman dalam Penyelesaian Sengketa di ASEAN, Uni Eropa dan Liga Arab - Margolang, Fahmi Ihsan; Zahrani, Rahma; Sapriliani, Syara; Mushlih, Taufik (Syekh Ali Hasan Ahmad Addary State Islamic University, 2024)
This study explores the role of cultural diversity in dispute resolution within ASEAN, the European Union, and the Arab League. Using a qualitative library research method, this study analyzes relevant literature through the lens of multiculturalism and regional integration theories. Multiculturalism emphasizes the importance of cultural recognition, while regional integration theories, such as neo-functionalism and intergovernmentalism, highlight the roles of supranational institutions and member states. The findings indicate that cultural diversity influences dispute resolution approaches in the three organizations. ASEAN prioritizes consensus, the European Union employs legal mechanisms, while the Arab League faces internal political challenges. This study concludes that cultural recognition and robust institutional frameworks are key to effective dispute resolution.